2015
DOI: 10.1128/mcb.01097-14
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Occupancy of STAT1 in Interferon Responses Is Regulated by Processive Transcription

Abstract: Interferons regulate immunity by inducing DNA binding of the transcription factor STAT1 through Y701 phosphorylation. Transcription by STAT1 needs to be restricted to minimize the adverse effects of prolonged immune responses. It remains unclear how STAT1 inactivation is regulated such that the transcription output is adequate. Here we show that efficient STAT1 inactivation in macrophages is coupled with processive transcription. Ongoing transcription feeds back to reduce the promoter occupancy of STAT1 and, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 47 publications
(58 reference statements)
5
12
0
Order By: Relevance
“…4a, b). Furthermore, we observed a weak association between STAT2 and STAT1 that, in line with earlier observations, did not increase after IFN-I treatment 22,23 . STAT1 and IRF9 could not be coprecipitated, despite earlier studies assigning transcriptional activity to STAT1–IRF9 complexes 25,26 .…”
Section: Resultssupporting
confidence: 92%
“…4a, b). Furthermore, we observed a weak association between STAT2 and STAT1 that, in line with earlier observations, did not increase after IFN-I treatment 22,23 . STAT1 and IRF9 could not be coprecipitated, despite earlier studies assigning transcriptional activity to STAT1–IRF9 complexes 25,26 .…”
Section: Resultssupporting
confidence: 92%
“…The STAT1 C-terminal TAD is also required for the recruitment of CDK8, a component of the Mediator kinase module, which has been implicated in multiple aspects of the transcriptional cycle, including transcriptional re-initiation (3). The recent finding that STAT1 requires processive transcription for its dephosphorylation and promoter dissociation (69) prompts the hypothesis that transcriptionally compromised STAT1β homodimers accumulate at the promoters and prevent transcriptional re-initiation. However, it is also possible that the time-dependent effects observed relate to the heterogeneity of the cell population and reflect an increase in the number of cells responding to IFNγ over time.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, nuclear STAT1 in infected cells appeared to be fully activated to a large extent, as revealed by the high levels of phosphorylation at Tyr 701 and Ser 727 . DNA‐bound STAT1 is indeed protected from dephosphorylation at Tyr 701 (Mertens et al, ; Meyer et al, ; Wiesauer, Gaumannmuller, Steinparzer, Strobl, & Kovarik, ) and has been reported to be required for phosphorylation at Ser 727 (Sadzak et al, ). Thus, high levels of phosphorylated STAT1 in the nuclei of T. gondii ‐infected cells clearly argue for a DNA‐bound state, thereby hindering nuclear export.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, nuclear STAT1 in infected cells appeared to be fully activated to a large extent, as revealed by the high levels of phosphorylation at Tyr 701 and Ser 727 . DNA-bound STAT1 is indeed protected from dephosphorylation at Tyr 701 (Mertens et al, 2006;Meyer et al, 2003;Wiesauer, Gaumannmuller, Steinparzer, Strobl, & Kovarik, 2015) and has been reported to be required for phosphorylation at Ser 727 (Sadzak et al, 2008 (Köster & Hauser, 1999) was cultured in DMEM supplemented with 10% FCS, 1-mM sodium pyruvate, non-essential amino acids, antibiotics as above, and 2.5 μg/ml puromycin. Immortilised primary murine fibroblasts expressing either wild-type STAT1 (STAT1 WT ) or mutant STAT1 with a Phe 77 -to-Ala substitution (STAT1 F77A ;Begitt et al, 2014;Meyer et al, 2004) were cultured in DMEM medium as specified above but without puromycin.…”
Section: Discussionmentioning
confidence: 99%